Changes in obliquity drive tree cover shifts in eastern tropical South America. (1st March 2022) - Ferreira, Jaqueline Q.; Chiessi, Cristiano M.; Hirota, Marina; Oliveira, Rafael S.; Prange, Matthias; Häggi, Christoph; Crivellari, Stefano; Nandini-Weiss, Sri D.; Bertassoli, Dailson J.; Campos, Marília C.; Mulitza, Stefan; Albuquerque, Ana Luiza S.; et al.
Abstract: Despite its great ecological importance, the main factors governing tree cover in tropical savannas as well as savanna-forest boundaries are still largely unknown. Here we address this issue by investigating marine sediment records of long-chain n -alkane stable carbon (δ 13 Cwax ) and hydrogen (δDwax ) isotopes from a core collected off eastern tropical South America spanning the last ca. 45 thousand years. While δ 13 Cwax is a proxy for the main photosynthetic pathway of terrestrial vegetation, tracking the relative proportion of C3 (mainly trees) versus C4 (mainly grasses) plants, δDwax is a proxy for continental precipitation, tracking the intensity of rainfall. The investigated core was collected off the mouth of the São Francisco River drainage basin, a tropical savanna-dominated region with dry austral autumn, winter and spring. On top of millennial-scale changes, driven by anomalies in the amount of precipitation associated with Heinrich Stadials, we identify a marked obliquity control over the expansion and contraction of tree and grass cover. During periods of maximum (minimum) obliquity, trees (grasses) reached maximum coverage. We suggest that maximum (minimum) obliquity decreased (increased) the length of the dry season allowing (hampering) the expansion of tree-dominated vegetation. Periods of maximum obliquity induced an anomalous heating (cooling) of the summer (winter) hemisphere that in combination with a delayed response of the climate system slightly increased autumn precipitation over the São Francisco River drainage basin, through a shift of the Intertropical Convergence Zone towards or further into the anomalously heated hemisphere. We found that atmospheric CO2 concentration has only a secondary effect on tree cover. Our results underline the importance of the dry season length as a governing factor in the long-term control of tree cover in tropical landscapes. Highlights: Obliquity influences hydroclimate and vegetation in eastern tropical South America. High obliquity decreases the dry season length. A short dry season allows the expansion of tree cover.